Direct numerical simulation of mass transfer in bubbly flows. (30th August 2018) - Deising, D.; Bothe, D.; Marschall, H.
Highlights: Extensive parameter study of species transfer from single rising bubbles. Deduction of improved Sherwood correlation for interfacial species transfer. Adaptive mesh refinement, load balancing and multi-criterion refinement. Improved algebraic Volume-Of-Fluid method using iso-surface reconstruction. Fux-based window technique/moving reference frame. Abstract: Process design, especially in the chemical industry, often requires a detailed understanding and accurate quantification of interfacial mass transfer. Experimental investigations, however, are often infeasible as required measurement quantities and locations are inaccessible. Thus, Direct Numerical Simulations (DNS) have become a viable tool for the detailed study of mass transfer processes. This paper presents a numerical modelling framework for the simulation of dilute species transfer based on an algebraic Volume-of-Fluid method, aiming at the deduction of an improved closure model for interfacial species transfer from single rising bubbles. To this end, the Continuous Species Transfer (CST) model [18] and state-of-the-art high performance computing techniques are employed.